Revealing Pre-service Foreign Language Teachersâ Imagined Professional Identity in Reflective Journals - Iswandari, Yuseva Ariyani (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2017)
This study reports types of imagined identities that pre-service foreign language teachers construct during their preparation of becoming teachers in a pre-service course named Micro Teaching. This course specifically facilitates pre-service teachers to implement some theories of teaching in the previous semesters into practice. Revealing what kinds of teachers they imagine in the future is believed to have greater impact on the pre-service teachersâ professional development (Chong & Low, 2009). The researcher analyzed 19 pre-service teachersâ reflective journals to find out their imagined professional identities. The identities were then coded using the framework of imagined professional identity by Xu (2013) that fell into three categories: language expert, learning facilitator, and spiritual guide. The result showed that the three categories appeared in their reflective journals. However, the dominant imagined identity constructed throughout the semester was teachers as learning facilitators. It indicates that the pre-service teachersâ concept of teaching is shifted from the traditional concept which emphasizes teacher control into recognition of self-initiated learning.Â DOI: https://doi.org/10.24071/llt.2017.200107